Attempt of Lawsuit by The Debtor to Delay The Implementation of The Auction of The Object of Liability - Muhammad Irvan Hidayana; Ilyas Ismail; Muazzin Muazzin (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
The auction lawsuit arises when there is dissatisfaction with the debtor where the claim before the auction is intended by the plaintiff to delay the auction and the lawsuit after the auction has very diverse motives that cause it. The type of research used is normative legal research with analytical approach and legislation approach. (statute approach). Data processing is carried out in a systematic way on written legal materials. The purpose of this study is to explain the causes and explain the legal protection for debtors as well as the legal consequences for delaying the implementation of the mortgage execution auction. The results of this study indicate that there is a loss experienced by the debtor for setting a low limit value in the implementation of the mortgage execution auction which is carried out by the KPKNL as the Auction Body. Every limit price determination is required to use or use an appraisal service in accordance with Article 36 number 93/PMK/2010 concerning Auction Implementation Guidelines. There are objections to the low auction limit value, the debtor files a lawsuit to the court to postpone the auction, so if the court has given a decision that has permanent legal force stating the auction being held is invalid and null and void.